Terminal Bifurcation of the Right Testicular Vein and Left Testicular Arterio-Venous Anastomosis - Nayak, BS; Rao, KGM; Shetty, SD; Sirasanagandla, SR; Kumar, N; Guru, A (Kathmandu University Medical Journal, 2015)
The testis is the organ upon which the survival of the human species depends. Abnormalities of testicular vessels may lead to loss of gametogenesis and hormone production. Reported here is a case of bilateral variations of the testicular vessels observed in a male cadaver during the first year MBBS dissection classes. The right testicular vein bifurcated into two veins just before its termination and both the branches terminated into the inferior vena cava. The left testicular artery arose from the abdominal aorta just above the level of origin of the inferior mesenteric artery. There was an arterio-venous anastomosis between the left testicular vein and the left testicular artery. The arterio-venous anastomosis might be functionally important as it can change the quality of the blood entering the testis. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12496 Kathmandu University Medical Journal Vol.11(2) 2013: 168-170